KONSEP UANG DALAM PERSPEKTIF EKONOMI ISLAM DAN KONVENSIONAL: KAJIAN KOMPARATIF BERBASIS LITERATUR - Ely Elsanti; Nanda Tiara Dewi, Putri Rahmawati, Rana Asmaul Latif, Suci Hayati (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to compare the concept of money in the perspectives of Islamic economics and conventional economics, as well as to identify the implications and challenges in implementing the Islamic economic system in Indonesia. In conventional economics, money is viewed as a commodity that can be bought and sold to generate profit through interest or usury. Conversely, in Islamic economics, money serves solely as a legitimate medium of exchange and cannot be used to generate profit that contradicts Sharia principles, such as usury. This study shows that while the conventional economic system promotes rapid economic growth, it often leads to economic instability and social inequality. On the other hand, Islamic economics, which prioritises justice, transparency, and fair risk sharing, has the potential to create a more sustainable and inclusive economic system. However, the implementation of Islamic economics in Indonesia still faces several challenges, including low sharia financial literacy, gaps in understanding among the public, and regulations that are not yet fully supportive. Nevertheless, with greater support from the government, Islamic financial institutions, and the public, the Islamic economic system holds promising prospects for contributing to a more equitable and sustainable economic growth in Indonesia in the future.